Pengaruh Hafalan Al-Quran Terhadap Prestasi Belajar Pada Mata Pelajaran Alquran Hadist Kelas XI MIA.1 MAN 2 Parepare - Mirhanah (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
The research was conducted in framework to determine the influence of Al Quran memorized to student learning achievement of XI natural science class MAN 2 Parepare. Learning achievement is a student’s attainment result from the learning is got at school in period which have been settled at Al Quran hadist lesson. While Al Quran hadist is the lesson which is inside it learn about Al Quran verses and hadist texts in order to comprehend Al Quran and Hadist content. This research was taken place in MAN 2 Parepare began in April to june with research sample was all students of XI MIA 1 class counted 23 persons. Data was taken by inquiry got from students. Method which was used was linear regretion analysis caorrelation product moment significant level 5%. Research of processing data was showed r count equal to 0,6270 with degree of freedom = 23-2=21 significant level 5 % resulted table 0,3932 it means hypothesis nothing (Ho) is rejected and alternative hypothesis (Ha) is accepted means there is influence Al Quran memorized to student’s learning achievement.